A simplified viterbi matching algorithm for word partition in visual speech processing - Foo, Say Wei (2009)
In this paper, a novel simplified Viterbi matching algorithm for sequence partition is presented. This method connects the states of different HMMs to model the observed sequence. The method is applied to visual speech processing to partition the word into visual speech elements. Experimental result shows that good accuracy is achieved with the proposed method.